NGHIÊN CỨU CHẾ TẠO SÁP PHỨC HỢP DÙNG TRONG SẢN XUẤT THUỐC NỔ NHŨ TƯƠNG - Hà, Ngọc Thiện; Vương, Văn Trường; Nguyễn, Đức Nghĩa; Nguyễn, Thọ Trường; Lê, Khắc Đạo (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDYING ON COMPOUND WAX USED IN THE MANUFACTURE OF EMULSION EXPLOSIVESCompound wax is an important component which plays role as fuel phase, emulsifier in the manufacture of emulsion explosives. In this article, we reported the results of studying on the effects of the content of span-80, paraffin, mineral oil in the compound wax to its emulsifying ability, density and porosity of emulsion explosives. Emulsify explosive produced on the compound wax SVN-01 (20% span-80, 40% paraffin, 25% vaselin and 15% mineral oil) was characterized as high explosive velocity, compressible degree of the lead cylinder. The stability of the explosive in 6 thermal cycles (24 hours at -18oC and 24 hours at +60oC) compared to the control sample of 3 thermal cycles.